1999
DOI: 10.1029/eo080i033p00365-01
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale eddy aswirl with data in Gulf of Alaska

Abstract: For the first time ever in the Gulf of Alaska, an anticyclonic mesoscale eddy's formation, migration, and transport have been observed and thoroughly documented. The eddy, Haida‐1998, was found to be one of an annual supply of eddies that transport fresh water and nutrients into the mid‐gulf from the Alaskan panhandle and the Canadian west coast. Haida‐1998's core had an unusually high elevation, making it one of the largest eddies ever observed in this region. Its strength is attributed to oceanic features as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 4 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…The MODAS analyses from 1998 confirm the presence of numerous eddies that are seen in the model results. On the basis of the same altimeter data, the intense mesoscale activity in the GoA during 1998 has previously been reported by Crawford and Whitney [1999].…”
Section: Summary and Concluding Remarkssupporting
confidence: 69%
See 1 more Smart Citation
“…The MODAS analyses from 1998 confirm the presence of numerous eddies that are seen in the model results. On the basis of the same altimeter data, the intense mesoscale activity in the GoA during 1998 has previously been reported by Crawford and Whitney [1999].…”
Section: Summary and Concluding Remarkssupporting
confidence: 69%
“… Matthews et al [1992] found large eddies similar to those inferred from in situ observations using data from the Geosat geodetic mission. Data from more recent altimeters have proven that the large anticyclonic eddies in the GoA may remain intact for a period well beyond 1 year [ Crawford and Whitney , 1999; Okkonen et al , 2001]. These eddies can also be observed in infrared radiometer images from satellites [ Thomson and Gower , 1998], but winter conditions in the GoA generally present few cloud‐free days.…”
Section: Introductionmentioning
confidence: 99%
“…The eddy detection methods are mainly categorized into three types: (1) methods based on eddy inherit parameters, such as the Okubo-Weiss (OW) method; (2) eddy geometry-based methods, including the eddy-induced sea level anomaly (SLA)-based method; and (3) hybrid methods, which use both physical parameters and flow pattern associated with eddies. The eddy tracking methods have attracted a great deal of attention to understand different scientific problems [10][11][12][13][14][15][16]. The first school of tracking methods is referred to as the similarity method.…”
Section: Introductionmentioning
confidence: 99%
“…, are predominantly anticyclonic, and are more commonly observed in spring (Crawford & Whitney, 1999). Modeling studies have suggested that such eddies near the shelf break are intensified by ENSO warm events (Melsom, Meyers, Hurlburt, Metzger, & O'Brien, 1999).…”
mentioning
confidence: 99%